2019
DOI: 10.1177/1741143219884686
|View full text |Cite
|
Sign up to set email alerts
|

International school principals: Routes to headship and key challenges of their role

Abstract: Although there is an extensive literature across a range of national contexts concerning the evolving role of the school leader, little has been written about the rapidly expanding world of international school leadership. This paper focuses on the top tier of leadership of international schools by drawing on semi-structured interviews with 12 school principals in Malaysia, during which they reflected on the nature of their job and the routes they had taken to headship. It is argued that although the overwhelm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Their work, which includes schools from several Asian countries, does not address the principal owner/board relationship. More recent work that discusses the role of an international school principal in Asia does cite governance and the business elements as challenges and notes the wide-ranging models of governance in international schools (Bailey & Gibson, 2019). Nevertheless, the sole piece of work we have located that specifically discusses international school principalowner relations in Asia is Machin (2014), where 3 of the 15 participants were from Malaysia (the others being in Thailand and China).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their work, which includes schools from several Asian countries, does not address the principal owner/board relationship. More recent work that discusses the role of an international school principal in Asia does cite governance and the business elements as challenges and notes the wide-ranging models of governance in international schools (Bailey & Gibson, 2019). Nevertheless, the sole piece of work we have located that specifically discusses international school principalowner relations in Asia is Machin (2014), where 3 of the 15 participants were from Malaysia (the others being in Thailand and China).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue of loneliness among school principals has been primarily discussed in the context of beginning their managerial career (Ahmed and Al-Dhuwaihi, 2020; Tahir et al , 2017). Several studies have examined reasons for why school principals experience loneliness at work and found that principals cite the burden of responsibility at work (Korumaz, 2016), their dissatisfaction with the frequency of meetings with colleagues (Campbell et al , 2006) and the lack of free time to build social networks outside of school (Bailey and Gibson, 2019). However, the implications of loneliness on school principals' well-being have not yet been adequately addressed.…”
Section: Literature Review: Loneliness In the Workplacementioning
confidence: 99%
“…The purpose of this paper is to analyse the socialization experiences of British satellite college principals in China and the challenges they face in their role. Utilizing Van Maanen and Schein's (1979) theoretical framework of organizational socialization, one of the most developed and long standing models of socialization (Ashforth, Saks, & Lee, 1998), along with literature in the field around challenges faced by principals in international schools (Bailey & Gibson, 2020;Blandford & Shaw, 2013). The research questions were: (i) How do principals experience organizational socialization into a British satellite college?…”
Section: Introductionmentioning
confidence: 99%
“…The success of such a business model has enabled parent schools to sell territory rights to educational entrepreneurs who have now built portfolios of 'satellite colleges' tied together under one single branded 'group' with the result that many such groups now have a head office in the region holding an intra-national "locus of control" (Gibson & Bailey, 2021, p. 6). Principals for the purpose of this study are defined as the top tier leader of the whole college (Nursery to Year 13) as other studies in the field of international top tier leadership (Bailey & Gibson, 2020;Gibson & Bailey, 2021;Howling, 2017;Machin, 2014) have utilized the same job title. In this paper I am considering principals' perceptions of the satellite college, the satellite college's branded group and the parent school as influences on the socialization of principals.…”
Section: Introductionmentioning
confidence: 99%